Employee Resistance And The [Agent Of] Change Management Model On The Juridical Implications Of PTN-BH Status - Mulyo Widodo Mulyo Widodo; Wahyu Beny Mukti Setiyawan Wahyu Beny Mukti Setiyawan; Siti Mursidah Siti Mursidah (Journal Of Social Science (JoSS), 2023)
Studies on Legal Entity State Universities (PTN-BH) in this decade are more related to the study of money management and student rejection. Trying to complement the study, this study tries to see the holistic management of PTN-BH through a change management approach and resistance of PTN-BH employees internally. Using a mix-method to obtain in-depth and massive data, finally this study found that emphasizing transition management in the work system, as well as the use of UNNES Rector's power as an agent of change is a good way to reduce resistance and increase support for the juridical implications of UNNES PTN-BH. In more detail, optimization of 86.17% of juridical support and reduction of resistance, amounting to 15,054% of UNNES PTN-BH status, can be bridged through integrative and inclusive management governance and good communication between structures and implementers. Based on these findings, this paper has provided a sensitive frame of mind and complemented previous studies on the change in the status of PTN-BLU (State University-Umunm Service Agency) to PTN-BH. In practical terms, this study has also become a strategic study for UNNES in determining the attitudes and steps needed.